Developing an assessment instrument for strengthening the Pancasila student profile in web-based middle school mathematics teaching - Hamdi, Syukrul; Murdiyani, Nila Mareta; Muhammad Fauzan; Hasan Djidu; Endar Chrisdiyanto; Zafrullah, Zafrullah (Universitas Hamzanwadi, 2024)
This study aims to develop an assessment instrument for strengthening students' Pancasila profile in middle school mathematics teaching, which teachers can use. This research follows a development process using the Plomp model, consisting of three phases. The respondents involved in this study were six experts in mathematics education and information technology, 23 middle school mathematics teachers, and 1,297 students. The research results show that Aiken's V value is 0.89, which exceeds the v-table of 0.630, indicating good validity. The Cronbach Alpha reliability analysis results indicate a strong outcome, with a value of 0.751. Confirmatory factor analysis using the R program showed significant factor loadings with a p-value < 0.05. Apart from that, the achievement percentage for all dimensions is in the good category, with an average achievement of 87.06%. These results prove that the assessment instrument developed is suitable for teachers to measure the strengthening of Pancasila student profiles in mathematics teaching at school. The developed instrument can be used as an effective evaluation tool in mathematics teaching to strengthen the Pancasila Learner Profile and help identify areas that require improvement in teaching to achieve a more balanced profile across all dimensions.